Pengaruh Implementasi Sistem Informasi Keuangan Daerah Terhadap Kualitas Pelayanan Internal : Peran Kecerdasan Emosional Sebagai Intervening Variable - Jamali, Jamali; Nurwahidah, Nurwahidah (Lembaga KITA, 2020)
This study investigates the effect of implementing a regional financial information system (SIKD) on the quality of internal services using emotional intelligence as an intervening variable. The research was conducted by the local government work unit (SKPD) in the Banda Aceh government. Data was collected through distributing questionnaires to 170 employees who were taken by proportional sampling according to SKPD. Using structural equation modeling as a data analysis model, the study found that the implementation of SIKD had a positive and significant effect on employee emotional intelligence and internal service quality. The existence of emotional intelligence not only has a significant effect on improving the quality of internal services, but also mediates the effect of implementing SIKD on the internal services quality of SKPD.Keywords: internal services quality, employee’s emotional intelligence, implementation of SIKD, Structural equation modeling